The meaning of relationship in Hemingway's "Hills Like White Elephant" - Susanty Susanty (Journal on English as a Foreign Language, 2012)
This article is intended to postulate the position of women described well by Hemingway as a girl called Jig in “Hills like White Elephants” as a marginal part of a patriarchal society. Difficulty is found in describing the exact nature of a man-woman relationship in Hemingway as the woman characters are so thinly portrayed. “Hills like White Elephants” suggests a relationship between the meaning of white elephants and the man’s attitude toward the unborn child. The relationship presents the representation of boredom, desperateness of life, the sense of lost happiness, and the awareness of the failure of love. The story also can be defined into a two-part theme. The first is a commentary about the way selfishness can corrupt a relationship. The second comments on life and what it means to bear life.